Wake up! : hip-hop Christianity and the Black church - Kirk-Duggan, Cheryl A.; Hall, Marlon (Nashville : Abingdon Press, 2011)
"Once seen as only advocating violence, Hip Hop can be the church's agent of salvation and praise to transform society. After looking at Hip Hop's sociohistorical context, including its African roots, Wake Up! shows how Hip Hop now embodies the worldview of growing numbers of youth and young adults in all churches. The book also examines the inherent religious themes embedded in Hip Hop music"--P. [4] of cover.
Preface: it's bigger than hip hop -- I'm bound to wreck your body and say turn the party out: physical bodies and embodiment -- Hip hop is dead: musical characteristics -- I used to lover her: God, hip hop, and spirituality -- G.O.D. (Gaining One's Definition): black church and black culture -- Put down the pimp stick to pick up the pulpit: the impact of hip hop on the black church -- Jesus walks: youth, the church, and the need for transformation.
Includes bibliographical references.
Description based on print version record.
Keywords: African American youth -- Religious life; Hip-hop -- Religious aspects -- Christianity; RELIGION / Christian Life / General; Electronic books